Four new homonyms in Erythraeidae (Acari: Actinedida) - Gabryś, Grzegorz (Muzeum i Instytut Zoologii PAN, 2000)
Leptus villosus Mihelèiè, 1964 is a junior secondary homonym of Leptus villosus (Berlese, 1910); Leptus errabundus nom. nov. is proposed as a replacement name for L. villosus Mihelèiè, 1964. Leptus calvatus Mihelèiè, 1958 is a junior primary homonym of Leptus calvatus Willmann, 1951; Leptus incertusnom. nov.is proposed as a replacement name for L. cal-vatus Mihelèiè, 1958. Leptus diversus Mihelèiè, 1958 is a junior primary homonym of Leptus diversus Mihelèiè, 1958; Leptus furibundus nom. nov. is proposed as a replacement name for L. diversus Mihelèiè, 1958. Leptus diversus var. variatus Mihelèiè, 1958 is raised to the species rank. Abrolophus longipes (Schweizer and Bader, 1963) comb. nov.is a junior primary homonym of Abrolophus longipes (Willmann, 1951) comb. nov.; Abrolophus baderinom. nov.is proposed as a replacement name for A. longipes (Schweizer and Bader, 1963).
Na s. red. błędny ISSN 0001-6454
Bibliogr. s. 66
S. 65-66 : 24 cm
Keywords: Erythraeidae -- nomenklatura [KABA]; Acari; Parasitengona; Erythraeidae